"Should offensively oriented players receive a salary premium in the national basketball association?". Issue 6 (12th April 2022) - Potter, Joel; Ehrlich, Justin A.
Abstract : Purpose: Since recent research has found that offensively oriented players receive a salary premium, the current study recognizes this observed premium might exist because offense is worth more in terms of revenue generation. Given the popular sports saying, "Offense sells tickets, defense wins championships, " the authors quantify whether offense really does sell more "tickets" than defense in the NBA. Design/methodology/approach: Using NBA team revenue data as well as team offensive and defensive win shares, the authors estimate several econometric specifications to test if teams generate more revenue for offensive wins compared to defensive wins. The authors also employ a multi-year free agency study to identify if NBA players receive more compensation for offensive production than they do for defensive production. Findings: The authors find no statistical difference in revenue generation from offense compared to defense. The authors confirm these findings both before and after revenue sharing. These results are also robust to alternative specifications. Therefore, the authors conclude that fans do not prefer offense to defense in terms of their spending. Contrary to previous research, the authors find no evidence of an offensive premium paid to NBA players. Originality/value: Based on their findings, offensively oriented players should not receive a salary premium. The clear implication for team decision makers is that offensive production should be compensated at a similar rate as defensive production. Since the authors do not find evidence of an offensive premium for offensive production, their research suggests a likely labor market equilibrium in the NBA for both profit-maximizing and win-maximizing teams.